Tests of intestinal mucosal hyperpermeability: Many diseases, many biomarkers and a bright future. (June 2019) - Webb, Dominic-Luc
Abstract: The number of disorders now linked to increased intestinal mucosal permeability implies that a substantial percent of the population is affected. Drug interventions targeting reduced tight junctional permeability are being pursued. Although hyper-permeability in itself is not a clinically recognized disease entity, its relationship to disease processes has driven interest in measuring, and even monitoring mucosal permeability in vivo . Along with improved knowledge of gut barrier physiology, advances have been made in tests and biomarkers of barrier function. Drawing from our experiences in the past decade, considerations and challenges faced in assessing in vivo intestinal permeability are discussed herein, along with indications of what the future might hold.